Chasm in primary care provision in a universal health system: Findings from a nationally representative survey of health facilities in Malaysia - Lim, H.M.; Sivasampu, S.; Khoo, E.M.; Mohamad Noh, K. (Public Library of Science, 2017)
Background: Malaysia has achieved universal health coverage since 1980s through the expansion of direct public provision, particularly in rural areas. However, no systematic examination of the rural-urban distribution of primary care services and resources has been conducted to date for policy impact evaluation. Methods: We conducted a national cross-sectional survey of 316 public and 597 private primary care clinics, selected through proportionate stratified random sampling, from June 2011 through February 2012. Using a questionnaire developed based on the World Health Organization toolkits on monitoring health systems strengthening, we examined the availability of primary care services/resources and the associations between service/resource availability and clinic ownership, locality, and patient load. Data were weighted for all analyses to account for the complex survey design and produce unbiased national estimates. Results: Private primary care clinics and doctors outnumbered their public counterparts by factors of 5.6 and 3.9, respectively, but the private clinics were significantly less well-equipped with basic facilities and provided a more limited range of services. Per capita densities of primary care clinics and workforce were higher in urban areas (2.2 clinics and 15.1 providers per 10,000 population in urban areas versus 1.1 clinics and 11.7 providers per 10,000 population in rural areas). Within the public sector, the distribution of health services and resources was unequal and strongly favored the urban clinics. Regression analysis revealed that rural clinics had lower availability of services and resources after adjusting for ownership and patient load, but the associations were not significant except for workforce availability (adjusted odds ratio [OR]: 0.82; 95% confidence interval [CI]: 0.71-0.96). Conclusions: Targeted primary care expansion in rural areas could be an effective first step towards achieving universal health coverage, especially in countries with limited healthcare resources. Nonetheless, geographic expansion alone is inadequate to achieve effective coverage in a dichotomous primary care system, and the role of the private sector in primary care delivery should not be overlooked.